RISK TAKING FOR ONESELF AND OTHERS: A STRUCTURAL MODEL APPROACH. - Vieider, Ferdinand M.; Villegas ‐ Palacio, Clara; Martinsson, Peter; Mejía, Milagros (Economic Inquiry, 2016)
Economic theory makes no predictions about social factors affecting decisions under risk. We examine situations in which a decision maker decides for herself and another person under conditions of payoff equality, and compare them to individual decisions. By estimating a structural model, we find that responsibility leaves utility curvature unaffected, but accentuates the subjective distortion of very small and very large probabilities for both gains and losses. We also find that responsibility reduces loss aversion, but that these results only obtain under some specific definitions of the latter. These results serve to generalize and reconcile some of the still largely contradictory findings in the literature. They also have implications for financial agency, which we discuss.